Clinical features of anxiety disorder in post-COVID-19 syndrome and finding of its predictors - Dmytro Boiko (Bogomolets National Medical University, 2021)
the article summarizes and describes clinical features of anxiety disorders in post-COVID-19 syndrome. Mental and neurological disorders occupy a leading place in the structure of post-COVID syndrome. Recent studies indicate an increase in the incidence of anxiety disorders in individuals with COVID-19. However, no clinical or laboratory features of the post-COVID anxiety disorders have been identified. Therefore, our study aimed to describe the clinical features of anxiety disorders in the post-COVID period and to develop a mathematical prognostic model to identify potential predictors of post-COVID anxiety disorder. We conducted a case-control clinical study, which included 145 males and females, which were divided into 2 groups, namely: group 1 - patients who became ill with COVID-19 during the last 6 months and group 2 - persons who were not ill with COVID-19 during the last 6 months. The clinical interview included the registration of symptoms of the debut and the time of the debut relative to the episode of COVID-19. The Beck anxiety inventory was used for the assessment of the overall level of anxiety. The State-trait anxiety inventory was used to assess  state and trait anxiety. Statistical analysis of the data was performed using the program EZR Statistics 1.54. Anxiety disorders during the first 6 months after COVID-19 develop more often than those who have not had the disease in the last six months. Patients who had COVID-19 in the last 5-24 weeks have an increased risk of anxiety disorders during this period and therefore require close medical supervision and sufficient awareness of the likely symptoms. People with a post-COVID anxiety disorder reported the presence of autonomic symptoms, including excessive sweating and tachycardia, a feeling of inner emptiness, as well as circadian rhythm disorders in the form of difficulty falling asleep and waking up at the desired time. It should be noted that the overall frequency of detection of anxiety disorders in the post-COVID period is increasing. It has been established that the risk of developing post-COVID disorder decreases with knowledge of the fact of contact with an infected person before the COVID onset  and increases with a heightened level of prior personal anxiety. Circadian rhythm disorders, in particular sleep phase shift and abnormal fatigue, may be predictors of post-COVID anxiety disorder.